2020
DOI: 10.3390/jcm9020578
|View full text |Cite
|
Sign up to set email alerts
|

Classic and Novel Biomarkers as Potential Predictors of Ventricular Arrhythmias and Sudden Cardiac Death

Abstract: Sudden cardiac death (SCD), most often induced by ventricular arrhythmias, is one of the main reasons for cardiovascular-related mortality. While coronary artery disease remains the leading cause of SCD, other pathologies like cardiomyopathies and, especially in the younger population, genetic disorders, are linked to arrhythmia-related mortality. Despite many efforts to enhance the efficiency of risk-stratification strategies, effective tools for risk assessment are still missing. Biomarkers have a major impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 150 publications
(175 reference statements)
0
13
0
2
Order By: Relevance
“…Therefore, although CRP levels might have been affected by statins, it was not as well-controlled as oxLDL or NT-proBNP. In this sense, while high BNP levels are associated with a worse prognosis in the general population [25] and in individuals with SCAD [30] or with a history of heart failure [26,31], the data on the association between CRP and cardiovascular disease are conflicting [32][33][34], likely because of the dependence of CRP on traditional CVR factors [35]. Therefore, multivariate regression analysis also demonstrated that the association between NT-proBNP and oxLDL was independent of CRP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, although CRP levels might have been affected by statins, it was not as well-controlled as oxLDL or NT-proBNP. In this sense, while high BNP levels are associated with a worse prognosis in the general population [25] and in individuals with SCAD [30] or with a history of heart failure [26,31], the data on the association between CRP and cardiovascular disease are conflicting [32][33][34], likely because of the dependence of CRP on traditional CVR factors [35]. Therefore, multivariate regression analysis also demonstrated that the association between NT-proBNP and oxLDL was independent of CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Related to the cellular effect of oxLDL, authors indicated that oxLDL induces apoptosis in neonatal rat cardiomyocytes [9,38,39] and increases the expression of BNP in the HL-1 atrial cell line [40]. NT-proBNP predicts first-onset cardiac arrhythmia and sudden cardiac death in patients [26,30], and also reflects malignant electrophysiological remodeling [32]. Both oxLDL and BNP are independent predictors of response to cardiac resynchronization in heart failure, and are reduced in response to therapy [41], but much less is known about the role of oxLDL in cardiac events such as ventricular arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on circRNAs as postmortem diagnostic biomarkers of SCD are lacking and face immense challenges, despite their tremendous potential as clinical CVD markers. An ideal biomarker needs to have high sensitivity and specificity, and should not be affected by many factors such as patient gender, age, lifestyle, and genetic background [ 124 ]. It would be even better if a biomarker could reflect the severity of the disease stage or even predict the outcome [ 26 ].…”
Section: Circrnas As Novel Biomarkers In Postmortem Scd Diagnosismentioning
confidence: 99%
“…Ventricular arrhythmias, which may degenerate into ventricular fibrillation and lead to sudden cardiac death, cause the worldwide loss of approximately 18 million lives each year (Shomanova et al, 2020). In addition, the most common sustained arrhythmia, atrial fibrillation (AF) is a major health burden in developed countries (Kavousi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%